The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1001/jamanetworkopen.2021.14234
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Anticoagulant Therapy Initiation for Incident Atrial Fibrillation by Race/Ethnicity Among Patients in the Veterans Health Administration System

Abstract: IMPORTANCE Atrial fibrillation is a common cardiac rhythm disturbance causing substantial morbidity and mortality that disproportionately affects racial/ethnic minority groups.Anticoagulation reduces stroke risk in atrial fibrillation, yet studies show it is underprescribed in racial/ethnic minority patients.OBJECTIVE To compare initiation of anticoagulant therapy by race/ethnicity for patients in the Veterans Health Administration (VA) system with atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 63 publications
9
68
0
Order By: Relevance
“…Social and personal factors that are part of the eFI and we have captured in our prediction model may partially explain this, such as patients requiring additional care, being housebound, or being socially vulnerable. Previous work has examined the association between ethnicity and OAC prescribing in the US [ 44 , 45 ], but little is known in the UK. A local cross-sectional study found that there were no clear differences in warfarin prescribing by ethnic group, using data from general practice records from south and east London from 2008 to 2011 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social and personal factors that are part of the eFI and we have captured in our prediction model may partially explain this, such as patients requiring additional care, being housebound, or being socially vulnerable. Previous work has examined the association between ethnicity and OAC prescribing in the US [ 44 , 45 ], but little is known in the UK. A local cross-sectional study found that there were no clear differences in warfarin prescribing by ethnic group, using data from general practice records from south and east London from 2008 to 2011 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cohort study used data from the Race, Ethnicity, and Anticoagulation Choice in Atrial Fibrillation (REACH-AF) cohort to compare rates and types of anticoagulant therapy among PEH vs non-PEH. 4 Using administrative and clinical data from the Veterans Health Administration (VA), we defined the REACH-AF cohort as patients with a new AF diagnosis between January 1, 2010, and December 31, 2020, continuous VA enrollment for 2 years before diagnosis, and an outpatient confirmatory AF diagnosis within 180 days of the index diagnosis (eFigure in the Supplement ). We excluded patients with valvular heart disease, cardiac ablation, hyperthyroidism, an anticoagulant prescription in the 2 years before the index diagnosis, or death or hospice care in the 90 days after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with AF, lower income and socioeconomic status have been associated with lower overall use of oral anticoagulant therapy and lower use of newer generation direct oral anticoagulants as well as with worse outcomes [16] , [17] , [18] , [19] . However, evidence on the association of income level with the utilization of AATs is limited.…”
Section: Introductionmentioning
confidence: 99%